Avaliação do fenômeno de fadiga e das propriedades elásticas de misturas asfálticas com diferentes ligantes em variadas temperaturas - Rossato, Fábio Pereira (2015)
It is certain that most of Brazilian highways are under unfavorable conditions of trafficability. Technological developments led to a large increase in load capacity of trucks, resulting in higher impacts on the highways. Another factor to be considered in this degradation process of pavements is climatic variations, very common in Brazil. Among many types of defects found on Brazilian highways, one deserves special attention, the fatigue cracking. Aiming to investigate this problem, this study aimed to study the fatigue phenomenon in laboratory for asphalt mixture used in the field (Av. Hélvio Basso, Santa Maria-RS) and evaluate in laboratory its possible improvement using polymer modified binder before to fatigue performance at three different temperatures: 10°C, 25°C and 35°C. Three asphalt mixtures were prepared in the la, two conventional binder used in the monitored section (CACAMPO asphalt content in the field, and CALAB 50/70 asphalt content obtained in laboratory dosage), and a third polymer modified binder with (CALAB 60/85-E). Mixtures reproduced in the laboratory were prepared according to the Marshall methodology and the materials were characterized according to traditional experiments. For all mixtures, the volumetric parameters were determined, stability, fluency, adhesion, Indirect Tensile Streght, Total Resilience Moduli and performance to fatigue by indirect tensile stress under controlled mode. These last three were held at the three test testing temperatures. In the laboratory, it was evident the improvement in thermal susceptibility properties and stability of the mixture by using the modified binder polymer, providing a blend less susceptible to variations in temperature and stable at high temperatures. The results obtained in the laboratory demonstrated the superiority of the mixture CALAB 60/85 E, for the three temperatures studied, with emphasis on the destructive tests at the higher temperature. The rigidity of the mixtures, measured by the resilience module, showed little influence by the use of the modified binder, however, showed very different behavior with variation in temperature. Regarding the fatigue performance, the modified blends proved to be far superior than the conventional mix, ensuring an increase in service life for the three temperatures studied, specially for the temperature of 35°C. The temperature variation of the test proved to be very crucial in the fatigue performance of the asphalt mixture, which is inversely proportional to the temperature increase. At the end of the study, it is concluded that the use of polymer modified binders for can be a great option to improve the performance of asphalt mixtures against the fatigue rupture mechanism and it can be used successfully in regions with large temperature variations. Thus, it is possible to ensure an increase in the service life of the asphalt layer and therefore to the pavement as a whole.